Application Status of Hadoop in Data Cloud Computing - Jiang, Pinpeng (International Journal of Computer Science and Information Technology, 2024)
This paper summarizes the Hadoop platform and its application in network public opinion analysis, and emphasizes the advantages of Hadoop in big data storage and processing, as well as the development of cloud computing technology and its importance in data collection, processing and analysis. This paper also discusses the core technologies based on Hadoop and Spark, including keyword retrieval, web crawler and text mining, which together constitute a comprehensive toolkit for analyzing and managing online public opinion.